2016
DOI: 10.3390/ijgi5060091
|View full text |Cite
|
Sign up to set email alerts
|

Towards Narrowing the Curation Gap—Theoretical Considerations and Lessons Learned from Decades of Practice

Abstract: Abstract:Research as a digital enterprise has created new, often poorly addressed challenges for the management and curation of research to ensure continuity, transparency, and accountability. There is a common misunderstanding that curation can be considered at a later point in the research cycle or delegated or that it is too burdensome or too expensive due to a lack of efficient tools. This creates a curation gap between research practice and curation needs. We argue that this gap can be narrowed if curator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The need for management and curation of research to ensure continuity, transparency and accountability has created new challenges that are often poorly addressed by the libraries (Sesartić et al, 2016). Hence, it is not by accident that activities, related to research data have been identified as top trends of academic library work not only in 2012 and 2014, but also in 2016, focussing in the latter case on professional development for librarians, providing Research Data Services (RDSs) (ACRL, 2012(ACRL, , 2014(ACRL, , 2016.…”
Section: The Challenge Of the New Research Environmentmentioning
confidence: 99%
“…The need for management and curation of research to ensure continuity, transparency and accountability has created new challenges that are often poorly addressed by the libraries (Sesartić et al, 2016). Hence, it is not by accident that activities, related to research data have been identified as top trends of academic library work not only in 2012 and 2014, but also in 2016, focussing in the latter case on professional development for librarians, providing Research Data Services (RDSs) (ACRL, 2012(ACRL, , 2014(ACRL, , 2016.…”
Section: The Challenge Of the New Research Environmentmentioning
confidence: 99%
“…Firstly, one of his post-docs involved in the operation could be hired to work with ETH Library's Digital Curation Team, and secondly, the discussion of the principles underlying this research group's archive recently led to a publication highlighting the general concepts behind their approach which had proven useful for almost three decades of research practice (Sesartić et al, 2016).…”
Section: Active Data Managementmentioning
confidence: 99%